The "axis of resistance": Iran's expansion in the Middle East is hitting a wall - Guido Steinberg (Stiftung Wissenschaft und Politik (SWP), 2021)
Since 2011 the Islamic Republic of Iran has significantly extended its influence in the Middle East. The expansion reached its apex in 2018. It has since entered a new phase in which Tehran, despite not suffering any strategic military setbacks, is hitting a wall. Iran's biggest fundamental problem is that a majority of its allies in Lebanon, Syria, Iraq and Yemen are primarily military and terrorist actors. They frequently succeed in armed confrontations. Yet they are subsequently incapable of ensuring political and economic stability. The best option for German and European policymakers is a strategy of containment so as to put an end to Iran's expansion in the four countries mentioned above, but also to acknowledge in the short term that Tehran and its allies are in a position of strength. Part of such a containment strategy would be to impose the most far-reaching isolation and sanctions possible on Iran's armed partners. This includes adding Lebanese Hezbollah, the Hezbollah Battalions, Asa'ib Ahl al-Haqq and other militias loyal to Iran, including their leaders, to all. Should Iranian institutions and actors involved in its policy of expansion in the Middle East also be listed as terrorists? The close ties between the Quds Corps - which is in charge of Iran's policy towards its Arab neighbours - and unequivocally terrorist organisations such as Lebanese Hezbollah suggest that this step is necessary.
Keywords: 320